The Resident Parent: Program Director Attitudes on Childbearing During Residency, Available Resources, and Opportunities for Improvement - Kassandra Carrion, BA; Shirley Chen, MD; Theresa Webster, MD; Catherine L. Ly, MD; Heather J. Furnas, MD; Dung H. Nguyen, MD, PharmD (Plastic and Reconstructive Surgery, Global Open)
Background:. Increased focus on wellness and diversity in surgical training has resulted in policy changes to support resident family planning. This study investigated program director (PD) knowledge and perceptions of accommodations for residents with or seeking to start families and their attitudes toward parenthood’s effect on resident performance. Methods:. A survey was sent to 88 plastic and reconstructive surgery integrated residency PDs in the United States. Results were compared with a 2017 PD survey that surveyed similar topics. Results:. A total of 34 PDs completed the survey (38.6%): 85.3% had children themselves, and 38.2% had children during residency. Most PDs were “unsure” about accommodations for nursing mothers during the in-service examination (64.7%) and written board examinations (76.5%), but 64.7% knew of accommodations for nursing mothers who were actively operating. Less than half (47.1%) were “unsure” about the financial support available for fertility treatment. PDs feel strongly that hospitals should provide childcare and allow 12 weeks of leave for childbearing residents. PDs believe their institution’s resident salary is sufficient to support 1 resident parent and 1 child. PDs from northeast programs disagree that resident unions will effectively advocate for reasonable parental leave and fertility support policies. Overall, PDs did not believe that trainee wellness was affected by having children during training regardless of childbearing status. Conclusions:. Although PDs are supportive of residents becoming parents, discrepancies remain about available services that support trainee parents. Further studies regarding outcomes of different policies for residents who become parents are warranted given the variety of reported accommodations and attitudes.